PERCEPTION OF FUTURE TEACHERS ABOUT MOTHER TONGUE EDUCATION IN BRAHUI LANGUAGE AT PRIMARY LEVEL - Zarina Waheed; Abdul Wahab; Waheed Bahadur (Al-Burz, 2020)
Brahui language has its own uniqueness and value as it is one of the oldest languages of Pakistan and considered as a Dravidian language. The purpose of this study was to explore the perception of future Brahui speaking teachers about mother tongue education in Brahui language at primary level in Balochistan. In this study, a qualitative approach was used. The research design was case study and site of the study was Sardar Bahadur Khan Women’s University Quetta. Semi-structure interviews were conducted from the Brahui speaking future teachers of B.Ed. (Hons.) 7th semester (5), M.A Education 3rd semester (5) and M.Phil. (5). The participants were selected through purposive sampling. Thematic analysis was used as method for data analysis. The data analysis revealed two main themes as need of Brahui mother tongue education in Brahui majority schools and teacher training for Brahui mother tongue education.